Fortification and bioaccessibility of saffron apocarotenoids in potato tubers - Gómez Gómez, Lourdes; Morote, Lucía; Frusciante, Sarah; Rambla, José Luis; Diretto, Gianfranco; Niza, Enrique; López-Jimenez, Alberto José; Mondejar, María; Rubio-Moraga, Ángela; Argandoña, Javier; Presa, Silvia; Martín-Belmonte, Alejandro; et al. (Frontiers in Nutrition, 2022)
Carotenoids are C40 isoprenoids with well-established roles in photosynthesis, pollination, photoprotection, and hormone biosynthesis. The enzymatic or ROS-induced cleavage of carotenoids generates a group of compounds named apocarotenoids, with an increasing interest by virtue of their metabolic, physiological, and ecological activities. Both classes are used industrially in a variety of fields as colorants, supplements, and bio-actives. Crocins and picrocrocin, two saffron apocarotenoids, are examples of high-value pigments utilized in the food, feed, and pharmaceutical industries. In this study, a unique construct was achieved, namely O6, which contains CsCCD2L, UGT74AD1, and UGT709G1 genes responsible for the biosynthesis of saffron apocarotenoids driven by a patatin promoter for the generation of potato tubers producing crocins and picrocrocin. Different tuber potatoes accumulated crocins and picrocrocin ranging from 19.41–360 to 105–800 μg/g DW, respectively, with crocetin, crocin 1 [(crocetin-(β-D-glucosyl)-ester)] and crocin 2 [(crocetin)-(β-D-glucosyl)-(β-D-glucosyl)-ester)] being the main compounds detected. The pattern of carotenoids and apocarotenoids were distinct between wild type and transgenic tubers and were related to changes in the expression of the pathway genes, especially from PSY2, CCD1, and CCD4. In addition, the engineered tubers showed higher antioxidant capacity, up to almost 4-fold more than the wild type, which is a promising sign for the potential health advantages of these lines. In order to better investigate these aspects, different cooking methods were applied, and each process displayed a significant impact on the retention of apocarotenoids. More in detail, the in vitro bioaccessibility of these metabolites was found to be higher in boiled potatoes (97.23%) compared to raw, baked, and fried ones (80.97, 78.96, and 76.18%, respectively). Overall, this work shows that potatoes can be engineered to accumulate saffron apocarotenoids that, when consumed, can potentially offer better health benefits. Moreover, the high bioaccessibility of these compounds revealed that potato is an excellent way to deliver crocins and picrocrocin, while also helping to improve its nutritional value.